2022
DOI: 10.1186/s12873-022-00590-z
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring cardiopulmonary resuscitation quality in emergency departments: a national survey in China on current knowledge, attitudes, and practices

Abstract: Background To investigate current knowledge, attitudes, and practices for CPR quality control among emergency physicians in Chinese tertiary hospitals. Methods Anonymous questionnaires were distributed to physicians in 75 tertiary hospitals in China between January and July 2018. Results A total of 1405 respondents answered the survey without obvious logical errors. Only 54.4% respondents knew all crit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
2
0
1
Order By: Relevance
“…Prognostic factors for CPR duration largely overlap with those for favorable outcomes [ 36 ]. Hence, monitoring and optimizing the prognostic factors for the duration of CPR can help to achieve the favorable outcomes [ 37 , 38 ]. This study highlighted the prognostic factors associated with the duration of CPR in patients undergoing ECPR following IHCA or OHCA.…”
Section: Discussionmentioning
confidence: 99%
“…Prognostic factors for CPR duration largely overlap with those for favorable outcomes [ 36 ]. Hence, monitoring and optimizing the prognostic factors for the duration of CPR can help to achieve the favorable outcomes [ 37 , 38 ]. This study highlighted the prognostic factors associated with the duration of CPR in patients undergoing ECPR following IHCA or OHCA.…”
Section: Discussionmentioning
confidence: 99%
“…Em outro estudo, Cheng et al, 6 utilizaram monitoramento em tempo real das manobras de RCP intra-hospitalar e as ações eram revistas e apresentadas em feedback semanal aos membros dos times de ressuscitação. 6 Zheng et al, 7 por meio de pesquisa com 1405 profissionais de 75 hospitais terciários na China, observaram que 91% reconheciam a necessidade de monitoramento da RCP e 67,3% entendiam que o principal problema durante a RCP era a qualidade das compressões torácicas, influenciada diretamente pela fadiga do operador. 7 Esta influência da fadiga foi também observada por Trowbridge et al, 8 que demonstraram redução significativa da profundidade das compressões torácicas dentro dos dois primeiros minutos do início das manobras de RCP, ressaltando a importância do revezamento de socorristas.…”
unclassified
“…In another study, Cheng et al 6 used real-time monitoring of in-hospital CPR maneuvers and the actions were reviewed and presented in weekly feedback to members of the resuscitation teams. 6 Zheng et al, 7 through a survey of 1405 professionals from 75 tertiary hospitals in China, observed that 91% recognized the need for CPR monitoring and 67.3% understood that the main problem during CPR was the quality of chest compressions, directly influenced by operator fatigue. 7 This influence of fatigue was also observed by Trowbridge et al, 8 who demonstrated a significant reduction in the depth of chest compressions within the first two minutes of starting CPR maneuvers, highlighting the importance of alternating rescuers.…”
mentioning
confidence: 99%